Oktatásszervezés járvány idején - Bárczi Zsófia (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Előadásomban a koronavírus-világjárványnak az oktatásszervezésre gyakorolt hatását járom körül a szlovákiai felsőoktatásban, kiemelt figyelmet fordítva a Nyitrai Konstantin Filozófus Egyetem oktatási gyakorlatára. Az előadásban ismertetem a szlovákiai felsőoktatásban alkalmazott járványkezelésistratégiákat, a hibrid majd az online oktatásra való átállás megvalósulását és újszerű tanítási és tanulási módszerek, valamint technikai megoldások bevezetését a Nyitrai Konstantin Filozófus Egyetemen. Előadásom utolsó részében a megváltozott oktatói és hallgatói magatartásformák és szokások kérdésével foglalkozom.

Abstract. In my presentation, I will discuss the impact of the coronavirus pandemic on the organisation of education in higher education in Slovakia, with a special focus on the educational practice of Constantine the Philosopher University in Nitra. In the presentation, I will describe the strategies used to manage the epidemic in Slovak higher education, the implementation of the transition to hybrid and then online education, furthermore the introduction of new teaching, learning methods and technical solutions at the Constantine the Philosopher University in Nitra. In the last part of my presentation I will address the issue of changing attitudes and habits of teachers and students.
Organising education in an epidemic
Keywords: krízishelyzetek; oktatásszervezés; járványkezelési stratégiák